2018
DOI: 10.1186/s12933-018-0799-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statins on fasting glucose in non-diabetic individuals: nationwide population-based health examination in Korea

Abstract: BackgroundIncreasing evidence suggest that statin therapy has a diabetogenic effect. Individual types of statin may have a different effect on glucose metabolism. Using the repeated nationwide population-based health screening data in Korea, we investigated the longitudinal changes in fasting glucose level of non-diabetic individuals by use of statins.MethodsFrom the National Health Screening Cohort, we included 379,865 non-diabetic individuals who had ≥ 2 health screening examinations with fasting blood gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 74 publications
0
34
1
5
Order By: Relevance
“…Regarding the issue of statins and glucose level, Kim et al reported that use of atorvastatin, rosuvastatin, pitavastatin and simvastatin had a significant association with increase in fasting glucose of non-diabetic individuals [43]. However, Jeong et al reported that administration of highest-dose pitavastatin did not increase the risk of new-onset diabetes in patients at high risk of developing diabetes [44].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the issue of statins and glucose level, Kim et al reported that use of atorvastatin, rosuvastatin, pitavastatin and simvastatin had a significant association with increase in fasting glucose of non-diabetic individuals [43]. However, Jeong et al reported that administration of highest-dose pitavastatin did not increase the risk of new-onset diabetes in patients at high risk of developing diabetes [44].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the different pharmaco-epidemic responses and characteristics of diabetes in Asians, the risk of new-onset diabetes following long-term statin use is likely to be heterogeneous among Asians. Furthermore, most previous studies on Asians have only used a single hospital center or health screening data that lacked external validity [11,12,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the issue of statins and glucose level, Kim et al reported that use of atorvastatin, rosuvastatin, pitavastatin and simvastatin had a signi cant association with increase in fasting glucose of nondiabetic individuals [43]. However, Jeong et al reported that administration of highest-dose pitavastatin did not increase the risk of new-onset diabetes in patients at high risk of developing diabetes [44].…”
Section: Discussionmentioning
confidence: 99%